Indoor air quality: a risk-based approach to health criteria for radon indoors. Summary report on a WHO Working Group Eilat, Israel, 28 March-4 April 1993 (Central European journal of public health, 1993)
The Working Group discussed to what extent exposure to radon is a public health risk. It reviewed data from epidemiological studies of the occupational exposure of miners and residential exposures, animal experiments and other relevant work. The Group confirmed radon to be a human carcinogen, and recommended that indoor situations where individual risks exceeded 10(-3) per year should always be considered severe, further risk reduction must be sought based on procedures such as the optimization and evaluation of available control techniques. The Group considered what guidance could be offered to national authorities, and whether risks from radon should be considered solely within the present radiation protection framework policies or be handled as a part of a more integrated framework of all environmental risks; a three-step management scheme was proposed. The Group then discussed the problem of risk communication as a part of assisting policy-makers to arrive at strategies best suited to their socioeconomic conditions. The report concludes with 22 recommendations.
Keywords: komunikace; Radon; Public Health; lidé; Air Pollution, Indoor; Health Education; Humans; Communication; zdravotní výchova; zdravotní politika; socioekonomické faktory; radon; Světová zdravotnická organizace; znečištění vzduchu ve vnitřním prostředí; Environmental Monitoring; rizikové faktory; monitorování životního prostředí; World Health Organization; Socioeconomic Factors; Health Policy; veřejné zdravotnictví; Risk Factors